New methods in mammary gland development and cancer: proteomics, epigenetics, symmetric division and metastasis - Bentires-Alj, Mohamed (BioMed Central, 2012)
The European Network for Breast Development and Cancer (ENBDC) meeting on 'Methods in Mammary Gland Development and Cancer' has become an annual international rendezvous for scientists with interests in the normal and neoplastic breast. The fourth meeting in this series, held in April in Weggis, Switzerland, focused on proteomics, epigenetics, symmetric division, and metastasis.